Reaksi Daya Tahan Kardiovaskular Atlet Terhadap Efek Intake Kafein - Arimbi Arimbi (Departement of Mathematics Education, 2024)
This research aims to provide information on the use of natural food ingredients, namely caffeine in coffee as a supplement to support athlete performance which is much better and safer for the body than the use of chemical drugs as long as it is not used as a doping method, so in this research we will look at the effect of giving coffee caffeine. before exercise on the athlete's VO2max ability. In the body, one of the effects caused by caffeine is to accelerate vasodilation of blood vessels, thereby allowing blood circulation throughout the body to be more optimal. The research method used was pre-experiment involving 25 respondents. From this research, the average value of athletes' VO2max ability before caffeine intervention was 41.02 ml/kg/min, while the average athlete's VO2max ability after caffeine intervention was 44.85 ml/kg/min. So it can be concluded that there was an increase in the average value of the athlete's VO2max ability after the caffeine intervention or in other words the administration of caffeine had an effect on the athlete's VO2max ability.